A TPU composite material and its preparation method and application

By using polyester polyurethane as a matrix in the TPU material, combining polyvinylidene fluoride resin and introducing specific components, the problem of degradation of TPU materials and corrosion on silicone rubber in an electrochemical environment is solved, and a TPU composite material with high alkali resistance and low silicone rubber corrosion is achieved.

CN115926438BActive Publication Date: 2025-03-25SHANGHAI KINGFA SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211660938.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-03-25
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The existing TPU materials have poor degradation performance in electrochemical environments and cause corrosion to silicone rubber, resulting in insufficient alkali resistance and low silicone rubber corrosion.

Method used

Polyester polyurethane is used as a matrix and polyvinylidene fluoride resin is compounded, and components such as maleimide, zinc borate, silicone masterbatch and plasticizer are introduced. Through complex component combination and process processing, the alkali resistance and low silicone rubber corrosion of the TPU composite material are improved.

Benefits of technology

The alkali resistance and low silicone rubber corrosion of TPU composite materials are significantly improved, ensuring the stability and performance of the material in an alkaline environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004012620530000051
    Figure BDA0004012620530000051
  • Figure BDA0004012620530000061
    Figure BDA0004012620530000061
  • Figure BDA0004012620530000062
    Figure BDA0004012620530000062
Patent Text Reader

Abstract

The invention discloses a TPU composite material and its preparation method and application, and relates to the field of polymer technology. The TPU composite material comprises the following components in parts by weight: 20-80 parts of polyurethane resin, 10-30 parts of polyvinylidene fluoride, 10-40 parts of glass fiber, 1-2 parts of maleimide, 2-5 parts of zinc borate, 1-5 parts of silicone masterbatch, 2-6 parts of plasticizer, 0.6-2.0 parts of auxiliary agent, wherein the polyurethane resin is polyester polyurethane, and the Shore hardness of the polyurethane resin is greater than 70A. The TPU composite material of the present invention is based on polyester polyurethane, and is compounded with polyvinylidene fluoride resin, while introducing components such as maleimide, zinc borate, silicone masterbatch, plasticizer, and not only has high alkali resistance, but also has high low silicone rubber corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer technology, and in particular to a TPU composite material and a preparation method and application thereof. Background Art

[0002] Modified TPU can be used in automotive connectors due to its low warpage and high toughness. Some sealing structures often come into contact with silicone rubber to achieve sealing performance. This working condition causes the TPU material to be exposed to the electrochemical environment, and NaOH solution is formed on the surface of the parts, resulting in poor degradation performance of the TPU. On the other hand, long-term contact will cause the TPU material to corrode the silicone rubber, resulting in reduced rubber resilience or even brittleness.

[0003] TPU is divided into polyether series and polyester series. Polyester TPU has high tensile strength, tear strength and wear resistance. However, modified polyester TPU is used on parts that are prone to forming electrochemical environments (low NaOH solution environments). Long-term contact with alkaline solutions will cause the material properties to decay sharply.

[0004] At present, there are many reports on how to improve the hydrolysis resistance of TPU. For example, patent CN 104231598A prepares a TPU film with high hydrolysis stability by adding epoxy resin 12-25 and polycarbodiimide 3-8 to TPU particles, so that the hydrolysis stability of the TPU film product is improved, and the mechanical property retention rate is greatly improved compared with the existing products; patent CN 109320804 B prepares a hydrolysis-resistant and low-pressure-strain TPU foam film by compounding polyvinyl chloride, nitrile rubber, nylon fiber, hydroxyapatite, plasticizer, etc. The TPU materials invented above are mainly used to improve the hydrolysis resistance, and the main way is to improve the hydrolysis resistance by adding carbodiimide and epoxy resin in high proportion, but no mention is made on how to improve the alkali resistance and low silicone rubber corrosion performance of the TPU material. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide an alkali-resistant, low-silicone-corrosion TPU composite material and a preparation method and application thereof.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: in the first aspect, a TPU composite material is provided, comprising the following components in parts by weight: 20-80 parts of polyurethane resin, 10-30 parts of polyvinylidene fluoride, 10-40 parts of glass fiber, 1-2 parts of maleimide, 2-5 parts of zinc borate, 1-5 parts of silicone masterbatch, 2-6 parts of plasticizer, 0.6-2.0 parts of additives, wherein the polyurethane resin is polyester polyurethane, and the hardness of the polyurethane resin is greater than 70A.

[0007] Among the components of the TPU composite material of the present invention, polyvinylidene fluoride resin, maleimide, zinc borate, silicone masterbatch and plasticizer are introduced into the matrix polyurethane resin for compounding, which can effectively improve the alkali resistance and low silicone rubber corrosion of the product; wherein polyvinylidene fluoride blocks the penetration of alkali solution, which can improve the barrier property and strength of the TPU composite material, thereby improving the alkali resistance of the product; the silicone masterbatch and the plasticizer are compounded to change the polarity of the surface of the TPU composite material, play a role in polar repulsion and blocking the alkali solution, reduce the compatibility of the TPU composite material with the alkali solution, and improve the alkali resistance of the TPU composite material; maleimide reduces the reaction activity and speed of the polyurethane resin by blocking and terminating free radicals, thereby improving the alkali resistance of the TPU composite material; , At the same time, it can reduce the corrosiveness of materials to silicone rubber; silicone masterbatch, as a substitute for silicone rubber, consumes H in advance. + , reduce the corrosion of materials to silicone rubber; zinc borate and maleimide are compounded to work together to improve the stability of each component in the TPU composite material, reduce the pH change of the polyurethane resin in a high temperature environment, and reduce the corrosion of the TPU composite material to silicone rubber.

[0008] As a preferred embodiment of the TPU composite material of the present invention, the Shore hardness of the polyurethane resin is 80A-68D.

[0009] The Shore hardness of the polyurethane resin has a great influence on the product. If the Shore hardness of the polyurethane resin is too low, the alkali resistance of the product will be significantly reduced. Therefore, the inventors prefer the Shore hardness of the polyurethane resin to be 80A-68D. The products prepared with the polyurethane data within the above range have excellent alkali resistance.

[0010] In the present invention, the Shore hardness of the polyurethane resin is obtained by testing according to ISO 868-2003 standard.

[0011] As a preferred embodiment of the TPU composite material of the present invention, the weight portion of the polyvinylidene fluoride is 15-20 parts.

[0012] In the present invention, the content of polyvinylidene fluoride affects the alkali resistance of the TPU composite material. If the content of polyvinylidene fluoride is too low or too high, the alkali resistance of the TPU composite material is significantly reduced. Preferably, the content of polyvinylidene fluoride is 15-20 parts by weight.

[0013] As a preferred embodiment of the TPU composite material of the present invention, the plasticizer is at least one of an epoxy fatty acid plasticizer and an ethylene-vinyl acetate-carbon monoxide terpolymer.

[0014] The present invention selects at least one of an epoxy fatty acid plasticizer and an ethylene-vinyl acetate-carbon monoxide terpolymer as a plasticizer. Compared with other plasticizers, the epoxy fatty acid plasticizer or the ethylene-vinyl acetate-carbon monoxide terpolymer can effectively improve the alkali resistance and silicone corrosion resistance of the TPU composite material.

[0015] As a preferred embodiment of the TPU composite material of the present invention, the matrix of the silicone masterbatch is PP or PE, and the silicone content is greater than 30%.

[0016] As a preferred embodiment of the TPU composite material of the present invention, the glass fiber is chopped glass fiber or continuous glass fiber.

[0017] Preferably, the glass is chopped glass fiber; more preferably, the chopped glass fiber is E glass fiber, wherein the alkali content of the E glass fiber is ≤1.0%, and the sizing agent content is 1.0-3.0%.

[0018] As a preferred embodiment of the TPU composite material of the present invention, the auxiliary agent is at least one of an antioxidant and a lubricant.

[0019] More preferably, the antioxidant is a hindered phenol antioxidant; and the lubricant is erucamide.

[0020] In a second aspect, a method for preparing a TPU composite material is provided, comprising the following steps:

[0021] S1: premixing polyurethane resin, polyvinylidene fluoride, maleimide, zinc borate, plasticizer and additives to obtain a premix;

[0022] S2: The premix and glass fiber obtained in step S1 are fed into a twin-screw extruder from different feeding ports for melt extrusion and granulation to obtain a TPU composite material.

[0023] As a preferred embodiment of the method for preparing the TPU composite material of the present invention, when the twin-screw extruder is melt-extruded for granulation, the set temperatures of the twin-screw extruder from the feeding port to the die are: zone one temperature 150-170°C, zone two temperature 170-190°C, zone three temperature 185-195°C, zone four temperature 190-200°C, zone five temperature 190-200°C, zone six temperature 190-200°C, zone seven temperature 190-200°C, zone eight temperature 190-200°C, zone nine temperature 190-200°C, zone ten temperature 190-200°C.

[0024] In a third aspect, a TPU composite material is provided for use in an automotive connector.

[0025] Compared with the prior art, the invention has the following beneficial effects: the invention provides a TPU composite material, which is based on polyester polyurethane and is compounded with polyvinylidene fluoride resin, and at the same time introduces components such as maleimide, zinc borate, silicone masterbatch, and plasticizer, and not only has high alkali resistance, but also has high low silicone rubber corrosion resistance. The invention also provides a preparation method of the TPU composite material and its application in the preparation of automotive connectors. DETAILED DESCRIPTION

[0026] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0027] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified. The antioxidants and lubricants used in all the examples and comparative examples of the present invention are exactly the same;

[0028] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0029] TPU1: Shore hardness 73D, HF-1071D, polyester type, Huafeng Group Co., Ltd.

[0030] TPU2: Shore hardness 68D, HF-1065D, polyester type, Huafeng Group Co., Ltd.

[0031] TPU3: Shore hardness 95A, HF-1095A, polyester type, Huafeng Group Co., Ltd.

[0032] TPU4: Shore hardness 85A, HF-1185A, polyester type, Huafeng Group Co., Ltd.

[0033] TPU5: Shore hardness 80A, HF-1280A, polyester type, Huafeng Group Co., Ltd.

[0034] TPU6: Shore hardness 75A, HF-1075AP, polyester type, Huafeng Group Co., Ltd.

[0035] TPU7: Shore hardness 95A, HF-4095A, polyether type, Huafeng Group Co., Ltd.

[0036] TPU8: Shore hardness 70A, HF-1070AP, polyester type, Huafeng Group Co., Ltd.

[0037] Polyvinylidene fluoride: PVDF 340, Arkema, France;

[0038] Plasticizer 1: ethylene-vinyl acetate-carbon monoxide terpolymer, Hubei Qifei Pharmaceutical Chemical Co., Ltd.;

[0039] Plasticizer 2: Epoxy fatty acid plasticizer, Suzhou Huace Environmental Protection Technology Co., Ltd.;

[0040] Plasticizer 3: dimethyl phthalate, Shandong Shouhua Chemical Co., Ltd.;

[0041] Glass fiber: ECS301HP-3-H, Chongqing International;

[0042] Zinc borate: commercially available;

[0043] Silicone masterbatch: MB50-002, PE matrix, 50% silicone content, Dow Corning;

[0044] Antioxidant: Antioxidant 1010, commercially available;

[0045] Lubricant: Erucic acid amide, commercially available.

[0046] Examples 1-21 and Comparative Examples 1-7

[0047] The components and weight proportions of the TPU composite materials of the embodiments and comparative examples are shown in Table 1-3. In Embodiment 1-21 and Comparative Example 1-7, the auxiliary agents are antioxidant 1010 and erucamide, and the mass ratio of antioxidant 1010 to erucamide is 1:1.

[0048] The preparation method of the TPU composite material of Examples 1-21 and Comparative Examples 1-7 comprises the following steps:

[0049] S1: premixing polyurethane resin, polyvinylidene fluoride, maleimide, zinc borate, plasticizer and additives to obtain a premix;

[0050] S2: adding the premix and glass fiber obtained in step S1 to a twin-screw extruder from different feeding ports for melt extrusion, and obtaining a TPU composite material through stranding, water cooling, air cooling and pelletizing; when the twin-screw extruder is melt-extruded and pelletized, the set temperatures of the twin-screw extruder from the feeding port to the die are: zone 1 temperature 150-170°C, zone 2 temperature 170-190°C, zone 3 temperature 185-195°C, zone 4 temperature 190-200°C, zone 5 temperature 190-200°C, zone 6 temperature 190-200°C, zone 7 temperature 190-200°C, zone 8 temperature 190-200°C, zone 9 temperature 190-200°C, and zone 10 temperature 190-200°C.

[0051] Table 1

[0052]

[0053] Table 2

[0054]

[0055]

[0056] Table 3

[0057]

[0058] Performance Testing

[0059] The TPU composite materials prepared in the examples and comparative examples were tested for performance according to the following method:

[0060] (1) Notched impact strength retention rate after alkali aging: The specimens were injection molded into samples that meet the notched impact strength test requirements of ISO527-1 / 2. One group of specimens was subjected to a notched impact strength test at 23°C. Another group of specimens was placed in 8% NaOH solution and aged at 50°C for 200h. The notched impact strength retention rate of the TPU composite materials after alkali aging was calculated.

[0061] (2) Silicone rebound rate: According to the ASTM D395 / 2B method, the TPU composite material was sandwiched between silicone sheets, compressed in a mold, and aged for 1008 h in a high temperature environment at 120°C. The silicone rebound rate after aging was tested.

[0062] The test results are shown in Table 4;

[0063] Table 4

[0064]

[0065]

[0066] The invention provides a TPU composite material, which takes polyester polyurethane as a matrix, is compounded with polyvinylidene fluoride resin, and simultaneously introduces components such as maleimide, zinc borate, silicone masterbatch, and plasticizer. The material not only has high alkali resistance, but also has high low silicone rubber corrosion performance.

[0067] It can be seen from Table 4 that the TPU composite material prepared in the embodiment of the present invention has an alkali-resistant notched impact strength retention rate of ≥75%, and a silicone rubber rebound rate of ≥73%.

[0068] It can be seen from Examples 1-6 and Comparative Example 1 that when the hardness of the polyurethane resin is greater than 80A, the alkali resistance of the TPU composite material is further improved; when the hardness of the polyurethane resin is ≤80A, the alkali resistance of the TPU composite material is significantly reduced.

[0069] From the comparison between Example 2 and Examples 7-8, it can be seen that when at least one of epoxy fatty acid plasticizer and ethylene-vinyl acetate-carbon monoxide terpolymer is selected as the plasticizer, the alkali resistance and low silicone rubber corrosion performance of the TPU composite material are better.

[0070] It can be seen from Example 2 and Examples 9-21 that changing the content of the components in the TPU composite material will affect the alkali resistance and low silicone rubber corrosion performance of the TPU composite material.

[0071] It can be seen from Example 2 and Comparative Examples 3-7 that when a certain component is missing in the TPU composite material, the alkali resistance and low silicone rubber corrosion performance of the TPU composite material will be affected; for example, when the plasticizer is missing, the alkali resistance of the TPU composite material is significantly reduced; when the polyvinylidene fluoride resin is missing, the low silicone rubber corrosion performance of the TPU composite material is slightly reduced, and the alkali resistance is greatly reduced; when maleimide is missing, the alkali resistance and low silicone rubber corrosion performance of the TPU composite material are significantly reduced; when zinc borate is missing, the alkali resistance of the TPU composite material is reduced, and the low silicone rubber corrosion performance is greatly reduced; when the silicone masterbatch is missing, the low silicone rubber corrosion performance of the TPU composite material is reduced, and the alkali resistance is greatly reduced.

[0072] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A TPU composite material, characterized in that: The invention comprises the following components in parts by weight: 20-80 parts of polyurethane resin, 10-30 parts of polyvinylidene fluoride, 10-40 parts of glass fiber, 1-2 parts of maleimide, 2-5 parts of zinc borate, 1-5 parts of silicone masterbatch, 2-6 parts of plasticizer, and 0.6-2.0 parts of auxiliary agent, wherein the polyurethane resin is polyester polyurethane, and the Shore hardness of the polyurethane resin is 80A-68D; The plasticizer is at least one of an epoxy fatty acid plasticizer and an ethylene-vinyl acetate-carbon monoxide terpolymer.

2. The TPU composite material according to claim 1, characterized in that The weight portion of the polyvinylidene fluoride is 15-20 parts.

3. The TPU composite material according to claim 1, characterized in that The base of the silicone masterbatch is PP or PE, and the silicone content is greater than 30%.

4. The TPU composite material according to claim 1, characterized in that The glass fibers are chopped glass fibers or continuous glass fibers.

5. The TPU composite material according to claim 1, characterized in that: The auxiliary agent is at least one of an antioxidant and a lubricant.

6. The method for preparing the TPU composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: premixing polyurethane resin, polyvinylidene fluoride, maleimide, zinc borate, plasticizer and additives to obtain a premix; S2: The premix and glass fiber obtained in step S1 are fed into a twin-screw extruder from different feeding ports for melt extrusion and granulation to obtain a TPU composite material.

7. The preparation method according to claim 6, characterized in that: When the twin-screw extruder is melt-extruded for granulation, the set temperatures of the twin-screw extruder from the feeding port to the die are: zone one temperature 150-170°C, zone two temperature 170-190°C, zone three temperature 185-195°C, zone four temperature 190-200°C, zone five temperature 190-200°C, zone six temperature 190-200°C, zone seven temperature 190-200°C, zone eight temperature 190-200°C, zone nine temperature 190-200°C, zone ten temperature 190-200°C.

8. Use of the TPU composite material according to any one of claims 1 to 5 in an automobile connector.

Citation Information

Patent Citations

  • TPU (thermoplastic polyurethane) film with high hydrolytic stability and preparation method of TPU film

    CN104231598A

  • A high hydrolysis-resistant, low-pressure variable TPU film and its preparation method

    CN109320804B

  • High-resilience TPE (thermoplastic elastomer) material and preparation method thereof

    CN103725027A

  • High-performance engineering plastic / polyester type TPU (thermoplastic polyurethane) alloy material and preparation method thereof

    CN103819829A